2021
DOI: 10.21149/12156
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in Mexican children 1 to 11 years of age: an update from the Ensanut 2018-19

Abstract: Objective. To evaluate vitamin D status and deficiency in Mexican children and related factors, with updated data from a representative national survey. Materials and methods. Data and serum samples of child participants were collected in the Ensanut 2018-19. The measurement 25-(OH)-D was obtained through chemiluminescence. Height and weight, as well as dietary information, were measured using a semi-quan­titative food frequency questionnaire and sociodemographic information. Results. Data of 4 691 children ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
(21 reference statements)
0
5
0
1
Order By: Relevance
“…Vitamin D and calcium intake was insufficient in most toddlers, and the frequency was similar in females and males. Other authors have also reported that toddlers have insufficient intake of vitamin D and calcium [24,28,29,33,34]. Vitamin D is mainly produced by endogenous synthesis in the skin from exposure to sunlight, and only 10% of vitamin D comes from the diet [33].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D and calcium intake was insufficient in most toddlers, and the frequency was similar in females and males. Other authors have also reported that toddlers have insufficient intake of vitamin D and calcium [24,28,29,33,34]. Vitamin D is mainly produced by endogenous synthesis in the skin from exposure to sunlight, and only 10% of vitamin D comes from the diet [33].…”
Section: Discussionmentioning
confidence: 99%
“…In the adjusted model, the pre-school-age children residing in urban areas exhibited two times higher odds for ID (OR=2.2, p=0.011) than those from a rural dwelling, while relatively older age and affiliation with Liconsa represented a lower risk for ID (OR=0.5, p<0.001 and OR=0. 23…”
Section: Iron Deficiencymentioning
confidence: 99%
“…Specific data on ZD and vitamin D deficiency (VDD) VDD will be presented in two separate articles. 23,24 Considering all serum data on vitamin and mineral nutritional status studied in Ensanut-2018-19 (ID, B12D, VADp, VDD), for all the children and ZD available only for pre-school-age children), 34% (95%CI 29.3-38.9) of pre-school-age children and 27.9% (95%CI 25.2-30.7) of school-age children in Mexico had at least one micronutrient deficiency (data not shown).…”
Section: Micronutrient Deficiency In Mexican Childrenmentioning
confidence: 99%
“…6 En Estados Unidos se reportan cifras altas que van de 30 a 70%; 7 en México se ha estimado una prevalencia de 16% en niños de dos a 12 años, 12 Mario E. Flores y asociados reportan cifras de hasta 25.9% en preescolares y 36.6% en pacientes en edad escolar. 13 La determinación de los niveles de vitamina D se basa en la medición de los niveles séricos de calcidiol 25(OH)D. Algunos autores clasifican estos niveles como: deficiente, normal o tóxico; otros lo dividen en suficiente o deficiente. Una de las clasificaciones más aceptadas es la que encontramos en la guía de práctica clínica del grupo de trabajo de la Sociedad de Endocrinología sobre vitamina D, donde se clasifica como deficiente menos de 20 ng/ml, insuficiente 20-30 ng/ml y suficiente mayor de 30 ng/ ml.…”
Section: Introductionunclassified